A Study on Awareness and Utilization of Kishori Shakti Yojana (KSY) Services among Adolescent Girls in Urban Area of Davanagere Taluk - Swathi S Aithal; Sandhya Rani Javalkar; Satish Ghatage (Medsci Publications, 2018)
Background: Adolescence is an intermediate phase of develop- ment between childhood and adulthood. In 2000, Kishori Shakti Yojana (KSY) was initiated with aim of improving nutrition, health status and empowerment of adolescent girls. Objective: To assess the awareness and utilization of KSY services among adolescent girls and the factors influencing them. Methodology: A community based cross-sectional study was con- ducted among adolescent girls of urban Davanagere. A house to house survey was conducted among 376 girls; the data was col- lected by interview method, analyzed using SPSS (v16). Results: The mean age of adolescent girls was14.21 years; only 123 (32.7%) knew about KSY services. Supplementary nutrition ser- vices were utilized by only 100 (26.5%) adolescent girls, 96 (25.5%) attended health education sessions, 44 (11.7%) received iron and folic acid tablets but none of them utilized vocational training ser- vices. Reasons for poor utilization were lack of awareness, lack of motivation to avail services and unsuitable timings. Conclusion: This study observed poor awareness and utilization of KSY services. The need of hour is to spread more awareness and increase participation of adolescent girls addressing at individual, family and community levels.